2016
DOI: 10.1016/j.athoracsur.2015.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Double Right Atrial Blood Cysts

Abstract: Blood cysts are exceedingly rare benign cardiac tumors, generally involving the cardiac valves. They are found mainly in the first month of life and in children and are very uncommon in adults. We present a rare case of double right atrium blood cysts, incidentally detected by transthoracic echocardiography in an 85-year old patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
0
11
0
3
Order By: Relevance
“…Blood cysts are often found incidentally during autopsy in up to 50% of cardiac valves of infants younger than 2 months of age [1]. They are often less than 1 mm in size, and have been reported to involve the mitral, tricuspid, aortic, and World Journal of Cardiovascular Surgery pulmonary valves, as well as the right atrium, right ventricle, and left ventricle [2]. In cases of large cysts, the reported complications include left ventricular outflow tract obstruction, valve dysfunction, ventricular dysfunction, and occlusion of a coronary artery, depending on the site of the tumor [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Blood cysts are often found incidentally during autopsy in up to 50% of cardiac valves of infants younger than 2 months of age [1]. They are often less than 1 mm in size, and have been reported to involve the mitral, tricuspid, aortic, and World Journal of Cardiovascular Surgery pulmonary valves, as well as the right atrium, right ventricle, and left ventricle [2]. In cases of large cysts, the reported complications include left ventricular outflow tract obstruction, valve dysfunction, ventricular dysfunction, and occlusion of a coronary artery, depending on the site of the tumor [2].…”
Section: Discussionmentioning
confidence: 99%
“…The exact origin of blood cysts is not well-understood. However, three hypotheses have been proposed: 1) blood cysts are formed by the entrapment and compression of blood in crevices that later become sealed off; 2) they arise from heteroplastic changes of the primitive pericardial mesothelial tissue; and 3) hypoxia, inflammation, and bleeding diathesis lead to the formation of these cysts [1] [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the first report by Elsasser in 1844, intracardiac blood cysts have been believed to be rare primary tumors in adults [1]. Common locations have been reported all over the endocardium of the heart, including the mitral, tricuspid, and pulmonary valves as well as papillary muscles [2,3]. Blood cysts from both ventricles and the atrial septum in the right atrium (RA) are seldom observed.…”
Section: Introductionmentioning
confidence: 99%